EDUCATORS PEDAGOGICAL COMPETENCE IN ONLINE LEARNING AND ITS IMPACT ON STUDENTS' LEARNING OUTCOMES - Sholikhun, Muhamad; Soraya, Zulfatus; Siswanto, Siswanto; Wafirah, Milna (PEDAGOGIK : JURNAL PENDIDIKAN, 2022)
Covid-19 has a tangible impact on the learning process, namely the necessity of implementing bold learning. Bold learning ultimately requires educators to be proficient in using technology, but not all educators are ready to use technology in learning. This condition causes learning during the COVID-19 pandemic to be less than optimal, resulting in low learning outcomes. This study was conducted with the aim of analyzing how the correlation between the pedagogic competence of educators and student learning outcomes during the covid-19 pandemic. This research includes quantitative research. Research data was collected using two techniques, namely questionnaires and technical documentation. Research data that has been collected is then analyzed using statistical analysis of Product Moment correlation. Based on the data analysis, it can be said that the relationship between the pedagogic competence of educators and student learning outcomes is significant and positive. The results of this study can be achieved if bold learning during the pandemic requires adequate pedagogic competence in improving student learning outcomes